Immanuel Kant's prolegomena to Any future Metaphysics - Logan, Beryl (London Routledge, 1996)
This collection of seminal essays on the Prolegomena provides the student of philosophy with an invaluable overview of the issues and problems raised by Kant. Starting with the Carus translation of Kant's work, the edition offers a substantive new introduction, six papers never before published together and a comprehensive bibliography. Special attention is paid to the relationship between Kant and David Hume, whose philosophical investigations, according to Kant's famous quote, first interrupted Kant's 'dogmatic slumber'.